The Impact of Leadership and Allowances on Employee Performance: A Study of Satpol PP Kebayoran Lama - Putra, Awang Darmawan; Fitri, Diin; Aprilia, Syifa (Scimadly Publishing, 2024)
This study examines the extent to which leadership and allowances affect civil servant performance. Adopting a quantitative research approach, data were collected through Google Forms using a Likert Scale (1-5), covering the entire population of 93 employees through saturated sampling technique. The analysis was conducted using Multiple Linear Regression with Statistical Production Service Solustion (SPSS). The findings indicate that leadership has a positive and significant impact on employee performance. Conversely, allowances do not show a significant effect. Moreover, leadership shows a more substantial effect on performance compared to allowances, as indicated by the standard coefficients, where leadership has a beta value of 0.439 compared to 0.310 for allowances. Based on these results, it is recommended that institutions prioritize employee feedback and provide tailored guidance and motivation, especially for those experiencing performance issues.